A PID-FEC mechanism using cross-layer approach for video transmission over multi-hop wireless networks. (23rd April 2019) - Han, Longzhe; Bao, Xuecai; Yu, Hongying; Zhu, Huasheng; Fan, Tanghuai; Zhao, Jia; Ryu, Yeonseung
Multi-hop wireless networks (MWNs) provide an important infrastructure for ubiquitous multimedia content access. However, the accumulated packet losses greatly decrease the quality of multimedia services, particularly video streaming services. In order to overcome packet losses in MWNs, in this paper we propose a proportional integral derivative control-based forward error correction (PID-FEC) mechanism to improve the quality of video streaming services. Our proposed method adopts the cross-layer approach, and leverages the functionalities of different network layers. The automatic repeat request (ARQ) on the media access control (MAC) layer is used as an indicator of packet losses. With the packet loss information, the redundancy rates are adaptively regulated based on the PID control algorithm. Experimental results, presented herein, show that the PID-FEC achieves a better quality of video streaming, as well as a higher FEC efficiency, as compared with conventional FEC schemes, over a variety of network conditions.